Human capital relatedness and mergers and acquisitions - Lee, Kyeong Hun; Mauer, David C.; Xu, Emma Qianying (Journal of Financial Economics, 2018)
We construct a measure of the pairwise relatedness of firms’ human capital to examine whether human capital relatedness is a key factor in mergers and acquisitions. We find that mergers are more likely and merger returns and postmerger performance are higher when firms have related human capital. These relations are stronger or only present in acquisitions where the merging firms do not operate in the same industries or product markets. Reductions in employment and wages following mergers with high human capital relatedness suggest that the merged firm has greater ability to layoff low quality and/or duplicate employees and reduce labor costs. We further show in a falsification test that human capital relatedness has no effect on acquiring firm returns in asset sales when little or no labor is transferred, which helps validate our measure of human capital relatedness.